Myristic acid alleviates hippocampal aging correlated with GABAergic signaling - Shang, Qi; Chen, Guifeng; Zhang, Peng; Zhao, Wenhua; Chen, Honglin; Yu, Die; Yu, Fuyong; Liu, Huiwen; Zhang, Xuelai; He, Jiahui; Yu, Xiang; Zhang, Zhida; et al. (Frontiers in Nutrition, 2022)
Previous studies have shown that myristic acid (MA), a saturated fatty acid, could promote the proliferation and differentiation of neural stem cells in vitro. However, the effect of MA on hippocampal neurons aging has not been reported in vivo. Here we employed 22-month-old naturally aged C57BL/6 mice to evaluate the effect and mechanism of MA on hippocampal aging. First, we examined a decreased exploration and spatial memory ability in aging mice using the open field test and Morris water maze. Consistently, aging mice showed degenerative hippocampal histomorphology by H&E and Nissl staining. In terms of mechanism, imbalance of GABRB2 and GABRA2 expression in aging mice might be involved in hippocampus aging by mRNA high throughput sequencing (mRNA-seq) and immunohistochemistry (IHC) validation. Then, we revealed that MA alleviated the damage of exploration and spatial memory ability and ameliorated degeneration and aging of hippocampal neurons. Meanwhile, MA downregulated GABRB2 and upregulated GABRA2 expression, indicating MA might alleviate hippocampal aging correlated with GABAergic signaling. In conclusion, our findings revealed MA alleviated hippocampal correlated with GABAergic signaling, which might provide insight into the treatment of aging-associated diseases.